(untitled) (Research, Society and Development, 2022)
Antiretroviral therapy (ART) coincides with the evidence of occurrence of chronic cardiovascular diseases of atherosclerotic origin, when associated with long-term therapy. The objective was to evaluate the relationship between atherosclerosis and the antiretroviral regimen use in the treatment of HIV-positive patients and to quantify the calcium score in this group, correlating it with the duration of ART use. This was a cross-sectional study of adult patients with HIV/AIDS, consecutively and non-randomly selected, asymptomatic from the cardiovascular point of view, from two reference services in outpatient care in the state of Sergipe, aged over 18 years and using antiretroviral therapy. Of the sample, 65.4% were male and 34.6% were female, with a mean age of 46 years. Coronary atherosclerosis, detected by the calcium score, was found in 24 patients (31.17%). The duration of antiretroviral therapy was related to atherosclerosis and there were significant differences between the different antiretroviral regimens. In addition, the results show an association between ART containing a protease inhibitor. Age and exposure time to ART use were significant in the presence of atherosclerosis. The p values were considered statistically significant in 100% of the variables analyzed and the challenge is to promote the prevention of cardiovascular risks to reduce the number of coronary events, and the profile traced with this collection will allow a more careful approach to these patients, especially in the character preventive care with HIV/AIDS patients in the state of Sergipe.